"Development of a New ElLSA Kit for the Diagnosis of Hydatidosis in Humans" - E Ghorbanalinezhad; M Assmar; N Piazak; A Khabiri (Tehran University of Medical Sciences, 2001)
Cystic hydatid disease (Hydatidosis) is the most serious tape-worm infection prevalent in the cattle and sheep raising area of the world. Hydatidosis in man (as an accidental host) caused by infection with the ova containing larval stage of Echinococcus spp. In the last decade different techniques have been employed for the serological diagnosis of hydatid disease, such as IHA, IFA, ELISA, CCLE (Counter Current Immuno Electrophoresis). The immunologic techniques used in this study were ELISA and CCIE. Since whole hydatid cyst fluid has been used as a source of antigen for serodiagnosis of hydatidosis. The result of examination of 30 patients that were surgically and pathologically proven to have hydatidosis was presented here. By appointing 1:100 serum liter ascut-off titer and using the crude antigen (concentration: 6 mµg/ml), sensitivity and specificity of the Elisa test were reported to be 93.3% and 96.6%,respectively. The Elisa was compared with CCLE in this study; it was found to have sensivity and specificity 90% and 100%,respectively. Finally, the result of our study showed that the ELISA kit designed in our study is easy to perform, not expensive, safe, and simple with good sensivity and specifity.